2020
DOI: 10.1002/lom3.10361
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing both denitrification and nitrogen consumption improves performance of stream diel N2 flux models

Abstract: There is keen interest to enhance denitrification within intervening aquatic habitats between agricultural areas and downstream aquatic ecosystems to reduce nitrogen (N) loading impacts to receiving ecosystems. We conducted a series of measurements to examine whole system in situ diel denitrification estimates in experimental ditch and stream environments using a Bayesian one-station diel N 2 flux model. Model estimates revealed complex patterns that indicate fluxes may be controlled by the balance of both N 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 84 publications
(112 reference statements)
3
7
0
Order By: Relevance
“…Integration of modelled rates across time during our simulated runoff events indicated that approximately 40% of measured N retention was associate with denitrification in cutgrass mesocosms (Table 5). Our estimated denitrification rates (564-620 mg m −2 ) were similar to previously reported daily rates based on sediment core incubations (142-1049 mg m −2 day −1 ) [18,19] and daily diel N 2 -N flux estimates (700-1000 mg m −2 day −1 ) from experimental ditches vegetated with rice cutgrass [37]. Estimates from this study were also similar to reported denitrification rates (220-1176 mg m −2 day −1 ) from vegetated ditches in Italy [11,17,20] and the Czech Republic [14].…”
Section: The Role Of Denitrification In Net Nitrogen Retention In Vegsupporting
confidence: 88%
See 2 more Smart Citations
“…Integration of modelled rates across time during our simulated runoff events indicated that approximately 40% of measured N retention was associate with denitrification in cutgrass mesocosms (Table 5). Our estimated denitrification rates (564-620 mg m −2 ) were similar to previously reported daily rates based on sediment core incubations (142-1049 mg m −2 day −1 ) [18,19] and daily diel N 2 -N flux estimates (700-1000 mg m −2 day −1 ) from experimental ditches vegetated with rice cutgrass [37]. Estimates from this study were also similar to reported denitrification rates (220-1176 mg m −2 day −1 ) from vegetated ditches in Italy [11,17,20] and the Czech Republic [14].…”
Section: The Role Of Denitrification In Net Nitrogen Retention In Vegsupporting
confidence: 88%
“…Soana et al [11] also demonstrated that sediment core incubations can account for as little as half of whole reach open-channel estimates of denitrification rates. Open-channel approaches to measuring denitrification potentially provide better estimates by integrating spatial and temporal heterogeneity of factors influencing denitrification at the reach scale but are highly dependent on factors that control the rates of gas transfer at the surface water interface [17,37,45]. While all methods of measuring denitrification in vegetated ditch environments are prone to different biases, our results, coupled with previous observations, provide strong support for denitrification serving as a dominant N removal pathway in vegetated ditches [11,[17][18][19].…”
Section: The Role Of Denitrification In Net Nitrogen Retention In Vegsupporting
confidence: 71%
See 1 more Smart Citation
“…Reach-scale metabolism rates were estimated based on changes in dissolved oxygen (O 2 ) through time with a two-station method [46,47]. The two-station method was appropriate due to expected low reaeration coefficients (K) and a short distance to source water which can confound dissolved gas flux estimates if experimental systems are not treated discretely [48,49]. We used 2 HOBO ® (U26-001, Onset ® Computer Corporation, Bourne, ME, USA) loggers placed in the middle of each ditch at upstream and downstream ends to measure dissolved O 2 and temperature at 15 min intervals during each 24 h nutrient loading event.…”
Section: Reach-scale Metabolism Estimatesmentioning
confidence: 99%
“…Using a polyvinyl chloride sampler, exetainer vials were overfilled 3x, preserved with zinc chloride (ZnCl 2 ), capped, and stored until analysis. We measured dissolved N 2 :Ar in dissolved gas samples with a Membrane Inlet Mass Spectrometer (MIMS) (Bay Instruments, Easton, MD, USA) [49,55] [43]. We developed and applied a correction factor to eliminate instrument specific O 2 interference with N 2 :Ar measurements which may have contributed to below equilibrium N 2 :Ar ratios observed during daytime hours [43,58].…”
Section: Denitrification Estimatesmentioning
confidence: 99%